2010
DOI: 10.1002/pca.1253
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterisation of secondary metabolites from Ixeris sonchifolia by the combined use of HPLC‐TOFMS and HPLC‐ITMS

Abstract: A global profile of I. sonchifolia constituents was described, which could be useful for the quality control of this herb and its related preparations. The employed combination of HPLC-TOFMS and HPLC-ITMS could also be a promising tool for the analysis of other herbal medicines containing sesquiterpene lactones, phenolic acids or flavonoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 21 publications
0
19
0
2
Order By: Relevance
“…The different processing methods of RA are responsible for the extent of antibacterial activity. In contrast to other processed products of RA, the salt and wheat bran-broiled products display the strongest antibacterial activity (Han et al, 2008;Shi et al, 2011). However, the mechanism of the change of pharmacological effects of processed RA is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The different processing methods of RA are responsible for the extent of antibacterial activity. In contrast to other processed products of RA, the salt and wheat bran-broiled products display the strongest antibacterial activity (Han et al, 2008;Shi et al, 2011). However, the mechanism of the change of pharmacological effects of processed RA is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The fragment ions of m/z 169, 151 and 125 were generated owing to the loss of C 6 H 10 O 5 , C 6 H 10 O 5 –H 2 O, and C 6 H 10 O 5 –CO 2 from the parent ion. All of the data indicated that compound 1 was gluco‐syringic acid (Shi, Lu, et al, ; Shi, Zhang, et al, ). Compound 2 ( t R = 8.254 min) released an [M − H] − ion of m/z 134.0472.…”
Section: Resultsmentioning
confidence: 99%
“…MS/MS spectral analysis of compound 3 showed that the product ion had an m/z value of 151, which was 18 Da lower than the parent ion, and was formed from the compound of m/z 169 by the loss of H 2 O. In addition, compound 3 showed that another product ion of m/z 125 was formed from the compound of m/z 169 by losing CO 2 (Shi, Lu, et al, ; Shi, Zhang, et al, ). Compound 4 ( t R = 26.106 min) yielded an [M − H] − ion of m/z 353.0874.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical compounds of this plant are sesquiterpene lactones, organic acids, flavonoids, and triterpenes [6][7][8][9]. Ixerin Z and 11,13α-dihydroixerin Z are the major sesquiterpene lactones [10], which have been reported to have various activities for instance, anti-inflammatory, anti-microbial, and anti-tumor activities [11,12].…”
Section: Introductionmentioning
confidence: 99%